Effectiveness of gliocladium virens in controlling Fusarium oxysporum F. sp. capsici disease on chilli plant - Astri Afriani; Maria Heviyanti; Fitra syawal Harahap (Talenta Publisher, 2019)
Wilt disease which is caused by Fusarium oxysporum f. sp. capsici is one of the importantdiseases in chili plants that can reduce growth, fruits yield, quality, and chili production. Thisfungus comes inside the vascular bundle through the root tissue and quickly colonizes in xylemvessels and causing typical wilt symptoms on plants. In line with the development of organicfarming systems, biological control by using biological agents is the prospective method incontrolling diseases on the plant. Gliocladium virens are one of the biological agents that obstruct thespreading of disease. The aim of this study was to determine the effectiveness of Gliocladiumvirens in controlling Fusarium oxysporum f. Sp. Capsici on chili plant. This research usedrandomized block design with two factors: 1 The Time application of Gliocladium virens (W)factor; 2. Dosages of Gliocladium virens (D). The results show that on the treatment time ofapplication of Gliocladium virens W1 of 0.06, W2 of 0.05, W3 of 0.09 and W4 of 0.08 were notsignificantly different. The treatment given Gliocladium virens disease intensity at week 3 waslower that is equal to 0.125% compared to without treatment of G. virens (D0) the intensity ofthe disease at week 3 was higher at 1%.